DESAIN AKTIVITAS PEMBELAJARAN UNTUK MENGEMBANGKAN KECERDASAN LOGIK-MATEMATIK ANAK USIA DINI - Sitti Fatimah S.Sirate, Muhammad Yaumi (JIV-Jurnal Ilmiah Visi, 2014)
The purpose of this study is to improve instructional activity desain, develop the kinds of activity, and integrate design components to instructional activities which can develop logic-mathematic intelligence of early-aged children. The study was conducted as from January through August 2014 employing colaborative action research method and involving 30 respondents/informen, 5 school supervisors, and 10 principals as collaborators. The data were collected using observation technique, group discussion, document study, que- sionaire, and test to be analyzed quantitatively and qualitatively. The research findings show the instructional activity design has encouraged the teachers to conduct survey of logic-mathematic intelligence, implement 8 kinds of instructional activities, and improve teachers’ competence in integrating design components. Learn- ers develop on the basis of their intelligence, talent, and interest.